2017
DOI: 10.1093/ejo/cjx072
|View full text |Cite
|
Sign up to set email alerts
|

Effect of different masticatory functional demands on the 3D mandibular condyle morphology of growing rats using posterior bite-blocks

Abstract: Both the bite-block appliance and weak masticatory muscle function reduced the volume at all regions of the condylar process, although the functional factor had a substantially greater effect. However, only the bite-block appliance affected the condylar process length. In the presence of both factors, an additive effect was found but no interaction detected.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 18 publications
0
11
0
Order By: Relevance
“…Young rats were 4 weeks old, which corresponds to the initial period of usage of the teeth, which finish erupting at 21 days, 36 while adult rats were 26 weeks old. Many studies report similar ages when evaluating young and adult rats 10–18,21,22,27–29,31,32 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Young rats were 4 weeks old, which corresponds to the initial period of usage of the teeth, which finish erupting at 21 days, 36 while adult rats were 26 weeks old. Many studies report similar ages when evaluating young and adult rats 10–18,21,22,27–29,31,32 …”
Section: Discussionmentioning
confidence: 99%
“…The scans were then reconstructed using the integrated scanner software by choosing the condylar process area as the region of interest with a voxel size 30 μm and a field of view (FOV) of 15.4 mm. The scans were then exported in DICOM format, analysed with Osirix® image analysis software, Geneva, Switzerland, and reoriented according to the base of the condylar process, defined by the AB line passing through the deepest points of the posterior mandibular notches, as previously described 28 (Figure 1). The following measurements were studied: condylar base width, condylar process height and condylar cross-sectional surface.…”
Section: Micro-ctmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study, to our knowledge, is the first to investigate changes in mouse craniofacial morphology due to prolonged, multi-generational exposure to SD using 3D GMA. Prior studies using animal models have analyzed craniofacial adaptation to SD and load reduction in a single generation using 2D linear measurements ( Corruccini and Beecher, 1982 ; Kiliaridis et al, 1985 ; Dias et al, 2011 ; Denes et al, 2013 , 2018 ; Anderson et al, 2014 ; Goto et al, 2015 ; Kono et al, 2017 ). Mice are preferred models because of the use of isogenic strains, tight environmental control of multiple specimens, relatively short gestation periods, and extensive information from prior genetic and environmental studies ( Fish, 2016 ; Liu, 2016 ; Van Otterloo et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, Larsson and Ronnerman (1981), as well as Janson and Hasund (1981), concluded that patients subjected to orthodontic treatment are not prone to temporomandibular disorders in later life. A recent study by Denes et al (2018) demonstrated that using a bite-block appliance leads to weak masticatory muscle function at all regions of the condylar process. Conversely, according to Maillard et al (2017), neuromuscular molding appliances have positive surgical, aesthetical, functional and socio-economic effects on the patients undergoing orthodontic treatment.…”
Section: Introductionmentioning
confidence: 99%